The Concentrate Feeds Supply chain in Uganda: emerging trends and implications on quality and access to smallholder farmers and chain efficiency - Lukuyu, B.; Baker, D.; Baltenweck, I.; Poole, J.; Kabi, F.; Katongole, C.; Nadiope, G.; Byarugaba, A.; Kugonza, J.; Wabwire, R. (East Africa Dairy Development, 2013)
The increasing effective demand for livestock products such as milk, meat and eggs in Uganda drives farmers to supplement their livestock with concentrates to improve on their productivity. In Uganda about 33% of the dairy farmers use compounded dairy concentrate feed while a sizeable percentage of households nearly 56% use feed ingredients such as maize bran and rice bran as straights (EADD, 2010). The annual production of compounded feeds by the commercial feed millers is estimated at about 75,000 tons with small scale mixers producing 40,000 ton (Graffham et al. 2003). In some areas farmers often supplement with compounded feeds aimed at maintaining the animals’ condition and sustaining production during the dry season (Lukuyu et al. 2009). However, Uganda is faced with serious problems related to availability of well formulated and balanced rations for adequate dairy cattle feeding. Despite an abundance of cereal grains and their by products such as maize and maize bran, sorghum, millet, rice bran and root crops (e.g. cassava) as energy concentrates as well as protein concentrates such as soybean, sunflower cakes, cottonseed cakes, peas and groundnuts, farmers have continued to lament about the high prices of commercial feeds and poor quality feeds (Nakiganda et al. 2005).